Selective recovery of yttrium oxide and yttrium-europium oxide particles from fluorescent wastes by solvent extraction, precipitation, and calcination - Bilen, Ayseguel; Birol, Burak; Sonmez, Mehmet Seref (SPRINGER, 2025)
Rare earth elements (REEs) such as yttrium, europium, and terbium are extracted from minerals like bastn & auml;site and monazite through complex, energy-intensive processes. Recycling these elements is crucial for reducing environmental impact, conserving resources, and ensuring a stable supply. This manuscript explores the selective separation of Y and Eu from a solution using various solvent extraction agents (Cyanex 272, 572, 923, D2EHPA, and Aliquat 336). Initially, the phosphor powder with a particle size of less than 45 mu m was dissolved in a 4 M HNO3 solution, followed by Ca precipitation using Na2SO4. Solvent extraction was then carried out with D2EHPA, which enabled a higher separation efficiency of Y and Eu. The pH, concentration, time, and O: A effects on both the loading and stripping stages were investigated. For the stripping step, the effect of the stripping agent (HCl, HNO3) on the selective recovery of Y (> 99% purity) or Y-Eu oxides was examined. At the pH value of 0.05, 20% ligand concentration, and 1:1 O: A ratio for 10 min, 88.50% of Y was selectively transferred to the organic phase (D2EHPA) in one step, leaving a considerable amount of Eu remained in the raffinate. After solvent extraction, the effects of temperature, time, stoichiometric ratio, and pH were investigated for precipitation. For precipitation, using oxalic acid at twice the stoichiometric ratio at 50 degrees C, 99.45% of Y and 98.82% of Eu were precipitated in 120 min as REE oxalates. The precipitated oxalates were calcined, at 500-1100 degree celsius for 2-8 h. With a calcination process conducted at 800 degree celsius for 2 h, all the REE oxalates were converted to REE oxide form. It was observed that without solvent extraction, a Y-Eu oxide containing 90.64% Y and 6.92% Eu was produced, whereas, after D2EHPA extraction, Y oxide with 99.17% purity was obtained.
Keywords: Rare earth oxide; Fluorescent red phosphor; D2EHPA; Y2O3; Recycling; RARE-EARTH-ELEMENTS; TRIVALENT LANTHANIDES; SEPARATION; LAMPS; METALS; ACID; CHEMISTRY; POWDERS; Environmental Sciences & Ecology